Cloud computing applications and platforms: a survey - Hindia, M.N.; Reza, A.W.; Dakkak, O.; Awang Nor, S.; Noordin, K.A. (2014)
The implementation of cloud computing application takes the higher necessity, especially after suffering from modern problems, such as providing proper funds for social service and purchasing programs. For that, the cloud computing applications propose a promising solution to solve such issues. In this paper, we will discuss the implemention of cloud computing over Smart Grid system; a reliable, cost effective guaranteed and efficient system, it is expected to be Long Term Evolution (LTE): which allows larger pieces of spectrum, or bands to be used furthermore with more coverage and less latency and the third technology is Vehicular network: which is an important research area because of unique features and applications that offers. In this survey, we will present an overview of the smart grid, LTE and the vehicular network when they get integrated with cloud computing, in addition we will highlight the open issues and research direction which faces these technologies with cloud computing implementing in terms of Energy management, Information management for smart grid. In terms of applying cloud computing platforms for 4G Networks to achieve specific criteria and finally in terms of Architectural formation and Privacy and security for Vehicular cloud computing.